PERHITUNGAN EFISIENSI RECOVERY BOILER PADA PT TOBA PULP LESTARI TBK - Erwinsyah Sipahutar; William Sutanto; Rudi Arif Candra; Faisal Irsan Pasaribu (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2022)
PT Toba Pulp Lestari, Tbk is one of the companies in Indonesia whose main activity is to produce pulp. The company uses eucalyptus wood as the main material. Broadly speaking, pulp making begins with the digesting process, which is the process of cooking chips with the addition of white liquor and steam. Then distributed to washing and screening, then O2 delignification which produces unbleached pulp. then bleached in the bleaching process in three stages. After that, the pulp is made into sheet pulp in the pulp machine process. In addition, the supporting process for producing the pulp, one of which is the recovery boiler. The recovery boiler has two functions, namely the main function as a steam generator and the side function of producing green liquor from recovery to be produced again into white liquor as a cooking liquid in the digester. The performance condition of an equipment can be measured based on the efficiency of an equipment. In thermodynamics, thermal efficiency is a dimensionless measure that shows the performance of thermal equipment such as internal combustion engines and so on.